Structural Insights into Salinosporamide a Mediated Inhibition of the Human 20S Proteasome - Hagen Sülzen; Pavla Fajtova; Anthony J. O’Donoghue; Jan Silhan; Evzen Boura (Molecules)
The 20S proteasome, a critical component of the ubiquitin–proteasome system, plays a central role in regulating protein degradation in eukaryotic cells. Marizomib (MZB), also known as salinosporamide A, is a natural γ-lactam-β-lactone compound derived from Salinispora tropica and is a potent 20S proteasome covalent inhibitor with demonstrated anticancer properties. Its broad-spectrum inhibition of all three proteasome subunits and its ability to cross the blood–brain barrier has made it a promising therapeutic candidate for glioblastoma. In addition to this, MZB also demonstrates significant inhibition against the 20S proteasome of Trichomonas vaginalis (Tv20S), a protozoan parasite, suggesting its potential for parasitic treatments. Here, we present the cryo-EM structure of the human 20S proteasome in complex with MZB at 2.55 Å resolution. This structure reveals the binding mode of MZB to all six catalytic subunits within the two β-rings of the 20S proteasome, providing a detailed molecular understanding of its irreversible inhibitory mechanism. These findings enhance the therapeutic potential of MZB for both cancer and parasitic diseases at the molecular level and highlight marine-derived natural products in targeting the proteasome for therapeutic applications.